Pengaruh Pendidikan Kesehatan Seks Remaja Melalui Media Leafleat Dan Tanya Jawab Terhadap Perubahan Pengetahuan Pada Santriwati Di Pondok Pesantren Al Mukmin Sukoharjo - Munaaya Fitriyya; Wijayanti Wijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The importance of adolescent sexual health education in Islamic boarding schools goes beyond being a preventive measure for reproductive health issues. It also aims to shape a balanced understanding in accordance with religious values. In this context, Al Mukmin Islamic Boarding School in Sukoharjo strives to make a positive contribution to the development and understanding of female students regarding sexual health while reinforcing the moral and religious values instilled in the boarding school. Through leaflets and Q&A sessions, it is hoped that female students can gain better knowledge about adolescent sexual health, including some aspects such as reproduction, self-protection, relevant religious norms, and the importance of open communication with parents or guardians. The using of these media is expected to have a positive impact on changing the knowledge of female students, subsequently influencing their behaviors and decisions related to sexual health. This study is an experimental research with a one-group pre-post test method. To assess the impact of adolescent sexual health education is through leaflets and Q&A sessions then tested by Wilcoxon test. This test is utilized due to the non-normal distribution of the research data. Non-probability sampling (quota sampling method) is employed for sample selection. The population of this study consists of 56 female students from class X at Al Mukmin Islamic Boarding School in Sukoharjo.There is an increase in the knowledge scores of female students after receiving adolescent sexual health education through leaflets and Q&A sessions. The average knowledge score of female students before the education (pretest) was 13.30 ± 14.27 with a median of 14.00 and a score range of 8. After the education (posttest), the average knowledge score increased to 19.56 ± 19.83 with a median of 20.00 and a score range of 2. This indicates an improvement in the knowledge of class X female students at Al Mukmin Islamic Boarding School after receive information or education about adolescent sexual health. The adolescent sexual health education provided has a significant impact on improving knowledge, or it could be said that adolescent sexual health education can improve female students' thinking abilities.